International Environmental Justice : Competing Claims and Perspectives. - Gordon, Frederick D. (Advanced topics in environmental science., 2012)
Environmental justice encompasses the fair treatment and meaningful involvement of all people - regardless of race, class or colour - with respect to the development, implementation and enforcement of environmental laws, regulations and policies that could negatively impact their lifestyles. The focus of this volume is to offer a critical perspective, which advances the idea that environmental management and human rights are inherently interrelated. This book offers a unique angle on this complex topic by providing an understanding of environmental justice from both a United States and an inte.